Spatial distribution of 222Rn concentrations and dose estimations in various waters - Erdogdu, Murat; Damla, Nevzat; Kara, Ayhan; Sahan, Halide; Isik, Umit; Tel, Eyyup; Sahan, Muhittin (Taylor & Francis Inc, 2016)
In this article, the levels of Rn-222 concentrations, annual effective doses, and excess lifetime cancer risk estimations were investigated for water samples in the city of Osmaniye, located in the southern part of Turkey. The measurements were conducted using a radon gas analyzer (AlphaGUARD PQ 2000 PRO). The arithmetic average of Rn-222 concentrations was 0.44 Bq.L-1 with a geometric standard deviation of 0.19 and geometric average 0.41Bq.L-1. The results obtained were compared with the findings of other studies. All measured radon concentrations were below the values recommended by the World Health Organization and the U.S. Environmental Protection Agency. The associated radiological parameters such as annual effective doses (AED) and excess lifetime cancer risk (ELCR) from consumption of these waters were calculated. The computed average annual effective doses for ingestion and inhalation as well as excess lifetime cancer risk were estimated to be 1.13 mu Sv.y(-1), 1.10 mu Sv.y(-1), and 3.95 x 10(-6), respectively. Rn-222 concentration, AED, and ELCR interpolated values of the region were determined and mapped using the Kriging method. The results of radon concentrations in this study provide a data baseline for future studies on subsequent evaluations of possible future environmental contamination of Osmaniye Province.
Keywords: radon; annual effective dose; excess lifetime cancer risk; water